Lipid rafts and redox regulation of cellular signaling in cholesterol induced atherosclerosis - YILMAZ, BETÜL; KARTAL ÖZER, NESRİN (My University, 2010)
Redox mediated signaling mechanisms play crucial roles in the pathogenesis of several cardiovascular diseases. Atherosclerosis is one of the most important disorders induced mainly by hypercholesterolemia. Oxidation products and related signaling mechanisms are found within the characteristic biomarkers of atherosclerosis. Several studies have shown that redox signaling via lipid rafts play a significant role in the regulation of pathogenesis of many diseases including atherosclerosis. This review attempts to summarize redox signaling and lipid rafts in hypercholesterolemia induced atherosclerosis. © 2010 Bentham Science Publishers Ltd.
Keywords: Atherosclerosis; Hypercholesterolemia; Lipid rafts; Reactive species; Redox regulation; Signaling